THE EFFECT OF PEER REVIEW ON TEACHING WRITING ORGANIZATION - Asri Siti Fatimah; Ratu Sarah Pujasari (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: This study aims at investigating the use of peer review technique on students‟ writing organization ability. It becomes important since the process of revising the structural framework of writing is frequently ignored by most of the students. In fact, it is a pivotal aspect to help them construct their writings and facilitate the reader to understand the text effortlessly. In this study, the students are encouraged to think critically by reading, analyzing and giving advice to their peers‟ writing. By doing so, this technique will provide them with the authentic audience which can increase their motivation to write well. Thus, peer revising checklist is distributed to the students in order to help them reviewing their peers‟ writing. Experimental study is used in this study. It is conducted in Writing 2 class consisting of 60 students in English Education Department Siliwangi University Tasikmalaya. The result indicates that peer review has significant influence on the students‟ writing organization ability.Keywords: peer-review, writing organization, English Department’s students